Environmental Performance in Accounting Literature: A Bibliometric Approach - Aziza, Nurna; Mardiah, Nursita (Jurnal Aplikasi Bisnis dan Manajemen, 2023)
One of the factors that cause environmental performance articles is debated because many researchers generate different results. This study aims to map research topics, identify keyword definitions, theory, methodology, and research settings, and give the agenda for further research. This research is a bibliometric analysis design. A total of 55 articles use from 1996-2020. The fifth stage of bibliometric analysis is defining keywords, initial search results, refining search results, compiling initial data, and analysing data. It raised 3 clusters VOSviewer, the red, green, and blue clusters. The results show that the main point on the VOSviewer map is environmental performance (research topic) in the red zone cluster one. Define environmental performance as the results of the organization in managing its environmental impact. The theoretical point of view, the theory of legitimacy and stakeholder, has been used to explain this phenomenon. This study identifies the predominance of quantitative approaches to environmental performance and finds the most typical subjects are the United States and developed countries. The articles reviewed were mainly carried out in developed countries (60%) and to a lesser extent in developing countries (40%), mainly Asian countries such as Indonesia, Malaysia, and China. Keywords: Bibliometric analysis, decision-making, environmental performance, mapping, VOSviewer